Beliefs of Pentecostal pastors on the use of antiretroviral treatment among Pentecostal Christians living with HIV in a suburb of Cape Town-South Africa: a community health systems lens - Azia, Ivo Nchendia; Nyembezi, Anam; Carelse, Shernaaz; Mukumbang, Ferdinand C (Oxford University Press, 2025)
The global public health community accepts antiretroviral therapy (ART) for controlling and managing human immunodeficiency virus (HIV). However, within some communities, claims of faith or miraculous healing of HIV and acquired immunodeficiency syndrome (AIDS) by Pentecostal pastors continue to spark controversies. This paper reports on an exploratory qualitative study to explore the beliefs held by Pentecostal pastors regarding the use of ART among Pentecostal Christians who are living with HIV. Twenty (20) purposively selected Pentecostal pastors from two informal settlements in Cape Town, South Africa, participated in the study. Open-ended, semi-structured, in-depth individual interviews were conducted on their religious beliefs concerning ART adherence. Interviews were conducted in English, audiotaped and transcribed verbatim before being imported into the Atlas.ti 2023 software program for thematic data analysis. Since our study was guided by the relational community health system model a hybrid deductive-inductive thematic analysis was used. Two contrasting themes about the influence of the religious beliefs of Pentecostal pastors were identified. The first theme and its associated subthemes highlight the lack of basic HIV and ART knowledge among pastors. Consequently, these pastors tend to nudge their Christians to rely more on faith and spiritual healing at the expense of adherence to ART. The second theme and its related sub-themes suggest that some pastors possess some basic HIV knowledge and understand the role of ART and how it works. This group of pastors advise their congregants to use ART and other healthcare services in tandem with spiritual rituals, faith and prayers. Our findings highlight the need for functional community-based structures, such as community health committees and health facility management committees, in settings where complex interaction within the belief systems, practices and norms of some stakeholders can influence people's health-seeking behaviours such as adherence to chronic medications like ART.